Perancangan Sistem Informasi Konsolidasi Integritas Rekam Medis Rawat Jalan BerbasisWeb Guna Menunjang Efektivitas Pengklaiman BPJS di Rumah Sakit Hermina Arcamanik Bandung - Fadilah, Ridho Akbar; Abdussalaam, Falaah; Yunengsih, Yuyun (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to make it easier for officers to consolidate and integrity the BPJS outpatient claim files that will be submitted by the Hospital to the BPJS. The type of research used by researchers is qualitative research with a descriptive nature because it tends to use analysis, process, foundation and meaning (subject perspective) which is more emphasized. Data collection techniques in research include observation and interviews. system development methods using methodsAgile to make it easier to adapt if changes occur in a project. . By implementing the designed system, the potential impact can be to reduce dependence on manual processes that are time consuming and prone to errors, an integrated information system will automatically ensure better data integrity, transparency and accountability in the BPJS claiming process, even though there are initial costs for the implementation and development of information systems, in the long term it will result in significant cost savings, and avoid sanctions and legal problems that could arise due to violations of applicable regulations in managing health data and BPJS claims.